Social Support and Post Traumatic Growth in Wives of Domestic Violence Victims: Coping Strategies as Mediators - Harry, Desty Dwi Kayanti; Soetikno, Naomi; Satyadi, Heryanti (Analitika: Jurnal Magister Psikologi UMA, 2024)
This Domestic violence experienced by wives is a traumatic event that has a negative impact. However, victims of domestic violence can experience positive changes after experiencing trauma (post traumatic growth). This study aims to examine the role of coping strategies as a mediator in the relationship between social support and PTG. The measuring instruments used were PTGI (α = .931), MSPSS (α = .941), Brief-COPE (α = .878) and PTSD Checklist DSM 5 (α = .940). Participants in this study were 118 wives who had experienced domestic violence in the form of physical violence, psychological violence, sexual violence or domestic neglect violence with an age range of 19-59 years. The results showed a significant positive relationship between social support and PTG (r=.412, p<0.01), a significant positive relationship between problem-focused coping (r=.436, p<0.01) and emotion-focused coping (r=.501, p<0.01) and PTG and an insignificant positive relationship between dysfunctional coping (r=.072) and PTG. Problem-focused coping (p<0.05, 95% CI [0.037, 0.185]) and emotion-focused (p<0.05, 95% CI [0.050, 0.188]) acted as mediators in the relationship between social support and PTG while dysfunctional coping (p<0.05, 95% CI [-0.012, 0.019]) did not act as a mediator. The benefits of this study help victims of domestic violence choose the right coping strategy. For the community, it increases their insight into the importance of social support from family, friends and other important people to help victims through the traumatic phase of domestic violence.